Designing interventions in dealing with issues confronting the cultivation of research culture in Malaysian universities - Abdul Rahman, Shukran (PESA Center of Political, Economic and Social Research, 2018)
Higher Education sector is one of key contributors for a country’s advancement, mandated to play strategic roles in training workforce, generate new knowledge and nurture innovation. Higher learning institutions or universities are instrumental in solving societal problems, and driving transformation in the society. Despite the available resources for academics to conduct research, there exist various challenges that disrupt the research culture in universities. This paper discusses issues confronting Malaysian academics on research and development (R&D) activities, and recommends specific interventions to improve R&D activities in Malaysian universities. The discussion is expected to enlighten higher education authority of issues that require attention, and in turn steer the direction of universities on R&D agenda.